Criminal Objectives Integrality in the Indonesian Criminal Justice System - Rofiq, Ahmad; Disemadi, Hari Sutra; Putra Jaya, Nyoman Serikat (Al-Risalah, 2019)
The integrality of the criminal justice system must be realized in every aspect of sub-systems, in substance, structure, and legal culture. In this respect, in the process of criminal justice, the three sub-systems’ integrality are required so that the criminal justice system is capable to produce fair legal decisions in the process of law enforcement in Indonesia. Until such a policy is undertaken, the law will always be harsh against the poor and weak against the rich. This paper discusses criminal objectives integrality in Indonesian criminal justice system and its influence in the integrated criminal justice system. Using a normative juridical method, this paper demonstrates that each sub-system of criminal justice (the Police, Prosecutors, Courts, and the prison) is in line with the main objectives of criminal law enforcement as found in various laws that govern the institutions.